Affective Teacher—Student Relationships and Students' Externalizing Behavior Problems: A Meta-Analysis - Lei, Hao; Cui, Yunhuo; Chiu, Ming Ming (Frontiers in Psychology, 2016)
This meta-analysis of 57 primary studies with 73,933 students shows strong links between affective teacherstudent relationships (TSRs) and students’ externalizing behavior problems (EBPs). Moreover, students’ culture, age, gender, and the report types of EBPs moderated these effects. The negative correlation between positive indicators of affective TSRs and students’ EBPs was stronger (a) among Western students than Eastern ones, (b) for students in the lower grades of primary school than for other students, (c) when rated by teachers or parents than by students or peers, and (d) among females than among males. In contrast, the positive correlation between negative indicators of affective TSRs and students’ EBPs was stronger (a) among Eastern students than Western ones, (b) for students in the higher grades of primary school than for other students, and (c) when rated by students or peers than by teachers or parents.